Analisis SWOT Pada Prospek Gadai Emas iB Barokah Bank Jatim Cabang Syariah Surabaya - Della Sukma Pitaloka; Tony Seno Aji (ITB AAS INDONESIA Surakarta, 2020)
At this time not only Bank Jatim Syariah has a gold pawning product, there are still many other banks and even Islamic pawnshops that also have similar products. Competitiveness between institutions is what causes the writer to be interested in conducting a study that aims to find out the prospects of the Bank Jatim Syariah gold pawning by carrying out internal analysis of the company to arrange a strategy using SWOT. This type of research uses descriptive qualitative research. Data collection techniques using observation, interviews and documentation. The results of the analysis used the EFAS-IFAS matrix, SWOT matrix and Cartesian diagram. The results of the study found that in order to have good prospects according to the SWOT calculation, the appropriate strategy according to the results of the Cartesian diagram is found in quadrant 1 where quadrant 1 is the SO strategy quadrant, and from the calculation of the combination of strategies it is also obtained if the highest value acquisition is in the combination of strategies SO with a acquisition value of 4.59